2020
DOI: 10.1037/tra0000478
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prolonged exposure on sleep and enhancing treatment outcomes with evidence-based sleep interventions: A pilot study.

Abstract: Insomnia and nightmares are central features of posttraumatic stress disorder (PTSD). However, often they are inadequately assessed and ineffectively resolved following gold-standard PTSD treatment. Here we: (a) evaluate effects of prolonged exposure (PE) on subjectively measured sleep and (b) present pilot results of an examination of whether adding sleep interventions (imagery rehearsal therapy [IRT] and cognitive-behavioral therapy for insomnia [CBT-I]) to PE improves treatment response, relative to PE alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 34 publications
6
52
0
1
Order By: Relevance
“…Second, our findings call for further investigation for the effectiveness of sleep-focused interventions in improving psychological outcomes among refugees. Mindfulness-based training has shown potential in reducing pre-sleep arousal and improving sleep quality (Hassirim, Lim, Lo, & Lim, 2019) and Cognitive Behavioural Therapy for Insomnia is effective in targeting sleep disturbance commonly seen in PTSD (Walters et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our findings call for further investigation for the effectiveness of sleep-focused interventions in improving psychological outcomes among refugees. Mindfulness-based training has shown potential in reducing pre-sleep arousal and improving sleep quality (Hassirim, Lim, Lo, & Lim, 2019) and Cognitive Behavioural Therapy for Insomnia is effective in targeting sleep disturbance commonly seen in PTSD (Walters et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, two studies have found sleep disturbance mediated the relationship between trauma exposure and PTSD symptoms among veterans (Picchioni et al, 2010) and military personnel (Steele, Germain, & Campbell, 2017). Sleep disturbance is also a predictor of PTSD treatment outcome and clinically addressing sleep disturbance can improve PTSD symptoms (Nappi, Drummond, & Hall, 2012;Walters et al, 2019). Wright et al (2011) longitudinally examined, among combat veterans, the relationship between sleep and PTSD symptoms.…”
Section: 叙利亚难民中创伤暴露 移民后压力 睡眠障碍和心理健康之间的关系的 纵向调查mentioning
confidence: 94%
“…To account for obvious sleep outside the reported lights-out/lights-on times, rest intervals could be extended up to 60 min either side. This process is similar to methods used in other actigraphy studies (Goldman et al, 2007; Straus et al, 2015; Walters et al, 2020).…”
Section: Methodsmentioning
confidence: 89%
“…Notably, brief behavioral treatment for insomnia (BBTI) has been found to consolidate sleep overnight and improve rest-activity stability in veterans with insomnia (Kanady et al, 2020). Presumably, full CBT for insomnia would accomplish the same goal, given the emphasis on maintaining regular sleep-wake schedules and the documented benefit of consolidating overnight sleep (Talbot et al, 2014; Taylor and Pruiksma, 2014; Walters et al, 2020). Bright light therapy would also be expected to perhaps even more directly address the impaired diurnal rhythms in these populations (Winkler et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation